Mechanical and Physical Properties of Cement Mortar with Recausticizing Solid Byproduct - Sijabat, Edwin Kristianto; Harmaji, Andrie; Hendriansyah, Hendriansyah (Semesta Teknika, 2024)
The Kraft process is a method used to make paper pulp. This method produces cooking residue that can be recycled again. The recausticizing process produces large amounts of by-products.This research utilizes solid waste from causticizing from the pulp industry as a partial substitute for Portland cement for mortar raw material to obtain a material with good mechanical properties. The solid waste was pulverized, then characterization of Loss on Ignition (LOI), Inductively Coupled Plasma (ICP), Titration, and Total Titrable Alkali was carried out. The percentage of solid waste resulting from recausticizing as a substitute for cement is 0-100%, with a water-cement ratio (w/c) of 0.3. The mixed material is then printed into a 50x50x50mm mold followed by drying using the moist curing method. The hardened samples were tested for Density, Porosity, Water Absorption, and Compressive Strength. Mortar with partial cement replacement with 20-100% solid waste recousticizing produces a compressive strength of 1.3-22.6 MPa. The resulting water absorption ranges from 14.59-31.35%.